Pneumonia caused by COVID-19 and the importance of diagnosis as a benefit for treatment (Research, Society and Development, 2021)
The present study aimed to describe cases of pneumonia caused by COVID-19 and the importance of diagnosis as a benefit for treatment. This is a descriptive, integrative review, qualitative study. The study was carried out from January to March 2021 and consisted of identifying the problem and objectives, elaborating the guiding question, searching the literature, evaluating the data, analyzing and synthesizing the data and discussing and presenting the results. The research questions were: "What is the relationship between pneumonia and COVID-19?", "What is the importance of the rapid diagnosis of COVID-19?" And "What is the treatment used in patients with pneumonia caused by COVID-19?". The inclusion criteria were: articles made available in full, available in Portuguese, Spanish and English and published between the years 2019 and 2021. The exclusion criteria were: incomplete articles, letters to the editor, debates, reviews, abstracts or published articles in annals of events, unavailable in full and duplicated. Initially, 346 studies with the proposed theme were considered; among these, 120 studies were excluded, according to the established exclusion criteria. After applying the inclusion criteria, 12 studies remained. The diagnosis of pneumonia due to covid-19 is possible through positive CRP-TR or the presence of high clinical suspicion (compatible clinic + favorable epidemiology) associated with CT with a bilateral peripheral ground-glass pattern of lower lobes. Epidemiological measures for infection control management should be carried out.